Cowden Syndrome: Serendipitous Diagnosis in Patients with Significant Breast Disease. Case Series and Literature Review. Issue 1 (25th November 2016) - Heaney, Roisin M.; Farrell, Michael; Stokes, Maurice; Gorey, Tom; Murray, Dylan
Abstract: Cowden syndrome (CS) is a multi‐system disease that carries an increased lifetime risk of developing certain cancers as well as benign neoplasms. The presence of features of CS in the general unaffected population results in difficulties in the recognition and diagnosis of this condition. Early diagnosis is essential to prevent the development of malignant neoplasms, yet despite the introduction of diagnostic criteria and risk calculators, accurate diagnosis remains a challenge. We identified three patients who presented to the symptomatic breast unit of a University Teaching Hospital over a period of 12 weeks who subsequently were diagnosed with CS. In this article, we discuss their clinical presentations as well as their path to diagnosis. The short timeframe between the presentations of these patients undoubtedly expedited their diagnosis. Upon application of internationally recognized diagnostic criteria, only two out of our three patients were accurately diagnosed. The risk of breast cancer in CS is comparable with that found in Hereditary Breast and Ovarian Cancer Syndrome and while a protocol for breast screening in these patients exists in most centres, no such protocol exists for patients with CS in our institution. The recommended cancer surveillance programs for patients with CS have not been found to prolong survival, however. CS consists of a vast array of diseases that span the various specialties and the subsequent varied phenotypic presentation poses diagnostic difficulties for clinicians as emphasized in our series. Continued research is required to improve recognition and diagnosis and will hopefully result in the emergence of life prolonging strategies.